2023
DOI: 10.1038/s41529-022-00314-5
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition at emergent grain boundaries studied by DFT for 2-mercaptobenzothiazole on bi-crystalline copper

Abstract: Inhibition of the initiation of intergranular corrosion was modeled at the atomic scale for 2-mercaptobenzothiazole (MBT) adsorbed on a (110)-oriented copper bi-crystal exposing an emergent Σ9 coincident site lattice (CSL) grain boundary (GB) using dispersion-corrected density functional theory (DFT-D). At both isolated molecule and full, dense monolayer coverages, the molecule adsorbed on the grain and GB sites stands perpendicular or tilted with no parallel orientation to the surface being favored. Chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The first reason for this lack of chloride effect in the strongly acidic environment is that since most of the effects observed relate to the low pH of the electrolyte and the dominant thione conformer of the inhibitor, the effect of the chloride ions is relatively weaker and therefore masked by the strong pH effect. The second reason is that the bonding between the thione conformer of the 2-MBT molecules and the metallic substrate is rather strong and the 2-MBT layer densely covers the entire surface, including the residual oxidized regions as confirmed by DFT modelling [32,33], thus hindering the penetration of the chloride ions. On the other hand, in an alkaline environment of pH between 13 to 14, the thiolate form of the 2-MBT molecule (Figure 6c) is dominant [24,46].…”
Section: Influence Of Environment On the Adsorption Of 2-mbtmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reason for this lack of chloride effect in the strongly acidic environment is that since most of the effects observed relate to the low pH of the electrolyte and the dominant thione conformer of the inhibitor, the effect of the chloride ions is relatively weaker and therefore masked by the strong pH effect. The second reason is that the bonding between the thione conformer of the 2-MBT molecules and the metallic substrate is rather strong and the 2-MBT layer densely covers the entire surface, including the residual oxidized regions as confirmed by DFT modelling [32,33], thus hindering the penetration of the chloride ions. On the other hand, in an alkaline environment of pH between 13 to 14, the thiolate form of the 2-MBT molecule (Figure 6c) is dominant [24,46].…”
Section: Influence Of Environment On the Adsorption Of 2-mbtmentioning
confidence: 99%
“…Density functional theory (DFT) modelling has shown that dense organic monolayers can form on Cu(I) oxide-covered surfaces. It also suggests that besides covalent bonding between the S atoms of the molecules and Cu(I) ions of the covering oxide, there can be a hydrogen bonding between the NH group of the molecule and the surface oxygen atoms (for the thione conformer), or between the N atom and the Cu(I) ions (for the thiolate conformer) [21,32,33].…”
Section: -Mercaptobenzothiazole (2-mbtmentioning
confidence: 99%
“…[23][24][25] Density functional theory (DFT) calculations have found that the bonding between the copper surface and the 2-MBT molecules occurs mostly via the two sulphur atoms of the molecule (in thione form) or via the exocyclic sulphur and the nitrogen atom (in thiolate form). 26,27 Nevertheless, the role played by the metallic or oxidized state of the surface, the pH of the solution, and other factors that can influence the bonding mechanism of the molecule to the surface, require further experimental investigation.…”
mentioning
confidence: 99%